PENERAPAN MODEL FUN LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IA SD NEGERI 76 PEKANBARU - Wiwik Afritayani; Zulkifli '; Hamizi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is motivated by the low student learning outcomes IPA CLASS iA Elementary School 76 Pekanbaru from 35 students who did not achieve a minimum completeness criteria (KKM) as many as 23 students with an average value of 75.0 and 12 of her students scored above the KKM. This study is a Classroom Action Research (CAR) conducted aims to improve learning outcomes grade science students Ia SD Negeri 76 Pekanbaru by applying the learning model learning fun. Data collection instruments in this thesis is the teacher and student activity sheets and learning outcomes. This thesis presents the results of learning from the first cycle, the second cycle shows the complete base score only 14 people or 40% and who did not complete 21 people or 60% with an average of 63.5. At UH I were completed were 18 people or 47% who did not complete 17 people or 60% with an average of 75.6. At UH II who completed 28 or 93% were not completed 7 people, or about 7% with an average of 86.77. An increase in the percentage of students who achieve at Deuteronomy Daily KKM I with a percentage of 60% or 18 students. On Day II replicates the percentage of 93% or 28 students. Activity of students in the first cycle, the second cycle at the first meeting with an average of 54.16%, a second meeting with an average of 66.66%, activity of teachers in the first cycle to the second cycle increased, because teachers deliver all materials in accordance with step -step existing on the RPP. The activities of teachers in the first cycle and second cycle at the first meeting with an average 58.33%, the second meeting with the average of 62.5%, the third meeting with the average of 83.3%, the fourth meeting with an average of 95, 83% .. The results in class 1a SDN 76 Pekanbaru prove that the application of learning models fun learning can improve learning outcomes IPA Ia grade students of SDN 76 Pekanbaru.Keywords : fun learning, the result of IPA